Teachers’ Readiness for Implementing Nigeria’s New Competency-Based Basic Education Curriculum in Gombe State - Musa , Mshelia Adamu; Yunisa, Abdulrahman; Biwai, Yahuza (Kashere Journal of Education, 2025)
This study investigated teachers’ readiness for implementing the competency-based Basic Education Curriculum in Gombe State. A descriptive survey research design was employed, and data were collected from a sample of 362 basic education teachers selected through multistage sampling. A validated questionnaire with a reliability coefficient of 0.84 was used to gather information on teachers’ awareness, attitudes, instructional practices and challenges related to curriculum implementation. Data were analysed using descriptive statistics. The findings showed that teachers possessed moderate awareness but limited understanding of the competency-based curriculum. Their attitudes toward the reform were generally positive, although concerns about workload and insufficient support were evident. Instructional practices partially reflected competency-based principles, with limited use of performance-based assessment and differentiated instruction. Teachers also faced significant challenges, including inadequate training, insufficient instructional resources, overcrowded classrooms and weak administrative support. The study concluded that while teachers are willing to implement the competency-based curriculum, their readiness is hindered by gaps in understanding and systemic constraints. It was recommended that teachers receive continuous training, schools be provided with adequate instructional materials, class sizes be reduced and administrative support strengthened to enhance effective implementation.